Integrating Independent Power Producers into Emerging Wholesale Power Markets - Woolf, Fiona; Halpern, Jonathan (World Bank, Washington, DC, 2014)
Many developing and industrial countries have sought to open their electricity industries to competition. In both contexts, policymakers and investors have to deal with the consequences of earlier, more partial sector liberalization measures. Foremost among these is the existence of long-term contracts with independent power producers (IPPs). The long-term nature of these contracts has complicated the introduction of more far-reaching sectoral reform designed to harness competitive market forces for the benefit of consumers. In developing countries, introducing competition is often coupled with breaking up and privatizing state-owned electricity monopolies. In this context, discussion of renegotiation of power purchase agreements has tended toward the polemical. At one end are those who resist any change, arguing that the "sanctity of contracts" precludes modification of contract terms. At the other end are those who favor governments taking coercive measures to modify existing contracts in the name of maximizing economic welfare and minimizing the burden of sector reform on consumers and on the state. Drawing on recent country experiences, the authors analyze alternative approaches to restructuring contracts and designing power markets to reduce rigidities and incentivize IPPs to participate more fully in wholesale power markets and to take on greater market risk. The authors conclude that forced market integration or forced contract negotiation have failed and are counterproductive. Conversely, in countries where IPPs provide a sizable proportion of generation capacity, ignoring market integration may result in insufficient market liquidity and discourage new entry, attenuating the scope for market forces to act for the benefit of consumers. Failure to adapt power purchase contracts and market rules imposes huge resource costs on the economy beyond the financial obligations consumers and taxpayers must bear. Based on recent experience, a combination of measures, including adaptation of specific market rules, contractual alternatives for enhancing market liquidity, contract buyout provisions, transitional financing mechanisms, and characteristics of the successor entity to the power purchaser, offer promising approaches for reconciling preexisting IPP contracts with new market structures and reducing the magnitude of above-market costs associated with such contracts.